A Study On the Relationship Between Religion And Ecological Environment Protection - LI, Bo (Journal of Research for Christianity in China (JRCC), 2025)
The deterioration of the ecological environment has become a common concern of the whole world, it includes not only global climate change, increasingly severe pollution of fresh water resources, destruction of the ozone layer, land desertification and sharp decline in biodiversity, but also a series of social problems caused by the sustainable consumption of renewable and non renewable resources. Religious doctrines have always been rich in the idea of harmony between man and nature. These doctrinal thoughts and practices have strong vitality and appeal in secular society. Through the study of the relationship between religion and ecological environment protection, this paper tries to find the fit point between religious doctrines and the concept of ecological civilization in secular society, so as to produce a better view of benefit for the protection of ecological environment in China.